Introduction to wave scattering, localization, and mesoscopic phenomena - Sheng, Ping, 1946- (Academic Press, 1995)
This book gives readers a coherent picture of waves in disordered media, including multiple scattered waves. The book is intended to be self-contained, with illustrated problems and solutions at the end of each chapter to serve the double purpose of filling out the technical and mathematical details and giving the students exercises if used as a course textbook. The study of wave behavior in disordered media has applications in: Condensed matter physics (semi and superconductor nanostructures and mesoscopic phenomena) Materials science/analytical chemistry (analysis of composite and crystalline structures and properties) Optics and electronics (microelectronic and optoelectronic devices) Geology (seismic exploration of Earths subsurface).